Papermaking trials in a pilot paper machine with a new silica coated PCC filler - Ferreira, Paulo J. (2016)
The results of the papermaking tests performed in paper sheets produced in a pilot paper machine using Eucalyptus globulus bleached kraft fibres and a new filler of silica-modified PCC obtained by the sol-gel method are presented. This new filler proved already to be advantageous at lab scale and its performance is now evaluated at a pilot scale. Its application in a pilot paper machine led to results better than those obtained at lab scale. For paper sheets containing ca. 26 wt% of PCC-silica filler, improvements of 40% were obtained for the tensile index when compared to papers produced with the reference PCC. The optical properties were negatively affected in a magnitude similar to that of the lab trials. The improvement of the paper mechanical properties as well as the decrease in the optical properties are explained by the better bonding between the hydroxyl groups of the silica attached to the PCC particles and those of the cellulosic fibres. The present article is of particular importance since it reveals the high potential of PCC-silica as filler for paper produced in a continuous paper machine.